Flu seasons during the period 2018-2023 in Sarajevo Canton, Bosnia and Herzegovina: possible impact of the SARS-CoV-2 pandemic on the influenza A and B virus circulation - Almedina Moro; Amela Dedeić Ljubović; Edina Zahirović; Selma Mutevelić; Suzana Arapčić; Goran Čerkez; Irma Salimović-Bešić (Medicinski glasnik, 2024)
Aim: During the pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), many countries reported a significant decrease in the prevalence of influenza virus cases. The study aimed to characterize the flu seasons from 2018 to 2023 in Sarajevo Canton, Bosnia and Herzegovina (B&H), and to assess the possible impact of the SARS-CoV-2 pandemic on the influenza A and B virus circulation. Methods: The CDC Human Influenza Virus Real-Time RT-PCR Diagnostic Panels were used for the detection of influenza virus A and B, and subtyping of influenza virus A (H1pdm09 virus and H3). The data for this regis-try-based retrospective study were collected at the Clinical Centre of the University of Sarajevo, Unit for Clinical Microbiology (the laboratory that acts as a referral for the detection and characterization of influenza virus and SARS-CoV-2 in Federation B&H). Results: In the 2018/2019 and 2019/2020, an equal percentage of positive cases was recorded (148/410; 36%, and 182/504; 36%, respectively). The absence of the influenza virus was observed in 2020/2021. During 2021/2022, influenza virus was detected among 19/104 (18%) patients and slightly increased in 2022/2023 (45/269; 17%). The switch of the influenza B virus lineage was observed. Conclusion: The SARS-CoV-2 virus had an impact on the prevalence of influenza virus infection among the population of the Sarajevo Canton, B&H. Since the interactions between these two viruses are not entirely clear, awareness of a possible threat to public health is crucial.
Keywords: molecular epidemi-ology; Real-Time RT-PCR; subtyping; virus